Assessing the Impact of Climate Change on Human Health: Status and Trends of Malaria and Diarrhea with Respect to Temperature and Rainfall Variability in Nepal - Badu, Manoj (Kathmandu University Journal of Science, Engineering and Technology, 2013)
The study on the status and trends of malarial and diarrheal diseases in the three ecological zones in Nepal viz. the Terai, Hills and Mountains shows mixed results in terms of occurrence of the number of incidences with observed rainfall and temperature variability. The total numbers of incidences of malarial cases in the country have significantly declined during the study period of 26 years (1982-2007). However, the occurrence of incidences of the disease increases during the last 6-7 years of the study period, particularly in the Hills and Mountains of Nepal, indicating that malarial incidences are spreading to newer locations at higher altitudes of the country that traditionally were considered malaria-free. Diarrhea, considered to be one of the leading ten diseases in Nepal, shows irregular behavior with temperature and rainfall variability based on the data consideration of 14 years (1994/95-2007/08). Although, in decreasing trend in all three geographic regions, the numbers of diarrheal incidences are highest in the Mountains, followed by the Hills and Terai. However, with observed trends of increasing temperature and irregular rainfall patterns across the country during the study period, the diarrheal incidences are predicted to rise in the future, owing to the development of more suitable conditions for the spread of the disease.